Effects of Surface Polarity on Nematic Liquid Crystal Alignment. Issue 1 (June 2014) - Kim, Young Ju; Bae, Jin Woo; Song, Kigook
Abstract Alignment of liquid crystal molecules on a polymer substrate depend on various molecular interactions at the interface between liquid crystal and substrate, such as dispersion forces, dipolar interactions, steric interactions, hydrogen bonding, and physical interactions due to distortion of orientation field of liquid crystals by grooved surface of the substrate. Among these interactions, dispersion force is regarded as a long‐range interaction and other interactions are regarded as short‐range interactions which do not extend beyond a few tens of angstrom. The homeotropic alignment mechanisms for nematic liquid crystals were studied on oxygen plasma treated glass substrates. The homogenous alignment was obtained for positive nematic liquid crystals whereas the homeotropic alignment for negative liquid crystals. Our studies provide experimental evidences showing that there is competing forces to determine the orientation of liquid crystals, and alignment can be controlled by adjusting the substrate polarity. Relations between anchoring transition of liquid crystals and the polarity of substrates were studied by observing liquid crystal alignment directions using polarized optical microscopy, conoscope, and FTIR spectroscopy. These studies provide experimental evidences showing that short‐range dipolar interactions and long‐range van der Waals interactions competitively control the orientation of the LC director.